(3GdNHGjG GdNajI ddeaGhVGJ GdPcjI (B/s - (3HjRhQ, Jhes; (3GdYGeQj, NGdO s ((3GdbGgQI(B: s (3OGQ GdaGQhb ddGSJKeGQGJ GdKbGajI(B, s, 2007)
(3jVe CacGQ hEQTGOGJ YedjI Mhd af GdJaGhV, GdJNWjW hGdEYOGO dYedjI GdJaGhV, adSaI GdJaGhV, CeKdI YedjI hJLGQH eajOI Mhd af GdJaGhV, af GdJaGhV ef NdGd GdefXhQ GdYGdejs
Keywords: (3GdeaGhVGJs